1999
DOI: 10.1007/s101570050019
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-pathological characterization of mesangial proliferative glomerulonephritis with predominant deposition of IgM

Abstract: Background. IgM nephropathy (IgMN) was first described in 1978 but whether IgMN is a distinct entity has not yet been confirmed. We tried to clarify the characteristics of IgMN on the basis of clinical and histological findings of patients who were treated and investigated by us. Methods. We evaluated 90 patients (group A) with mesangial proliferative glomerulonephritis (MesPGN) who exhibited more dominant mesangial deposits of IgM than of IgG and IgA. To clarify the significance of the IgM mesangial deposits,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 9 publications
2
11
1
1
Order By: Relevance
“…This is not in agreement with other studies [2,20,21] . However, there are others studies which are in agreement with our study results.…”
Section: Discussioncontrasting
confidence: 95%
“…This is not in agreement with other studies [2,20,21] . However, there are others studies which are in agreement with our study results.…”
Section: Discussioncontrasting
confidence: 95%
“…Moreover, 3 of 5 patients with FSGS developed end-stage renal failure, but none of the 5 patients with minimal lesions or 1 patient with lupus nephritis showed progressive renal dysfunction, although MPGN lesion was not detected according to the published report [12]. Kishimoto and Arakawa [13] also reported that MesPGN with mesangial IgM deposits demonstrated higher serum IgM level, lower glomerular filtration rate and serum CH50 level, higher level of proteinuria, and higher incidence of adhesion and duplication of capillary loops than MesPGN without mesangial IgM deposits, suggesting that predominant IgM deposition should be referred to as IgM nephropathy with impaired renal function and poor prognosis. In the present case, renal lesions developed and finally demonstrated pathological findings applicable to MPGN, but not FSGS or MesPGN.…”
Section: Discussionmentioning
confidence: 95%
“…Most of the studies have reported on prevalence of IgMN as frequency/ percentage of renal biopsies with diagnosis of IgMN reported from 2 % to 18.5 % in native biopsies (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Occasional cases of IgMN in transplant biopsies have also been reported (14).…”
Section: Epidemiologymentioning
confidence: 99%